2016
DOI: 10.47604/ijfa.153
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Portfolio Size on the Financial Performance of Portfolios of Investment Firms in Kenya

Abstract: Purpose The purpose of this study was to determine the effect of portfolio size on the financial performance of portfolios of investment firms in Kenya. Methodology: The research design adopted a descriptive survey study. This implied that the total population of this study is 90 firms as given by the Kenya Association of Investment Groups (KAIG). For representativeness purposes, the current study took a sample size of 50% of the population. This was 45 firms.  The study used secondary data from the financial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 13 publications
3
7
1
Order By: Relevance
“…Thus, the study fails to reject the null hypothesis. These results are contrary to Kimani and Aduda (2016) who revealed that Muema et al / International Journal of Finance & Banking Studies, Vol 10 No 3, 2021ISSN: 2147 Peer-reviewed Academic Journal published by SSBFNET with respect to copyright holders.…”
Section: Panel Regressioncontrasting
confidence: 83%
See 3 more Smart Citations
“…Thus, the study fails to reject the null hypothesis. These results are contrary to Kimani and Aduda (2016) who revealed that Muema et al / International Journal of Finance & Banking Studies, Vol 10 No 3, 2021ISSN: 2147 Peer-reviewed Academic Journal published by SSBFNET with respect to copyright holders.…”
Section: Panel Regressioncontrasting
confidence: 83%
“…Despite the dip in the financial performance of the above CIS there is inconclusive evidence indicating the effect of equity investments, bond investments on the Financial Performance of collective Investment Schemes in Kenya making this study key in filling this knowledge gap. Kimani and Aduda (2016) looked at portfolio size and profitability of Kenyan investment firms and found that stock portfolio then bonds and money markets produced the best returns. Kimeu (2015) investigated portfolio composition and returns of NSE-listed investment firms and found that bond investment, real estate and equity positively affected fiscal performance.…”
Section: Page106 Page106mentioning
confidence: 99%
See 2 more Smart Citations
“…The proposed model was tested in East African Capital Market (EACMs) which comprise Nairobi Securities Exchanges (NSE), Dar es salaam Stock Exchanges (DSE), Uganda Securities Exchanges (USE) and Rwanda Stock Exchanges (RSE). The selection of the region were influenced by its growth compare to another region in the continent (ADB, 2019), equity is the best stock to trade in the region, although brokers are not competitive, local investors within the national stock markets are less confident on trading equity stock rather they invest on government bonds (Kimani, Aduda and Mwangi, 2017) also, there is an ongoing project sponsored by World Bank to integrate EACMs in one trading platform (Biau, 2018), most important this study is unique on its kind to be conducted in the region.…”
Section: Figure 1: the Flow Of Technical Efficiencymentioning
confidence: 99%